2014
DOI: 10.1177/1933719114527353
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood Telomere Content Is Greater in Patients With Endometriosis Than in Controls

Abstract: Longer telomeres could be consistent with a stem cell origin of endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…However, the seemingly vigorous endometrial regulation of telomerase via ovarian hormones and the fact that TA levels are high and constitutively expressed in proliferating endometrial epithelial cells may be responsible for the apparently rare incidence of such transformation ( Zafrakas et al ., 2014 ; Ness et al ., 2015 ). TL in peripheral lymphocytes of women with endometriosis compared to healthy controls did not differ in our studies ( Hapangama et al ., 2008 ; Hapangama et al ., 2009 ) while others have reported longer telomeres in PBMCs from women with endometriosis ( Dracxler et al ., 2014 ). The reason for this observed difference could be attributed to the influence of different demographic features known to affect PMBC TL such as age, BMI and ethnicity.…”
Section: The Endometriummentioning
confidence: 92%
“…However, the seemingly vigorous endometrial regulation of telomerase via ovarian hormones and the fact that TA levels are high and constitutively expressed in proliferating endometrial epithelial cells may be responsible for the apparently rare incidence of such transformation ( Zafrakas et al ., 2014 ; Ness et al ., 2015 ). TL in peripheral lymphocytes of women with endometriosis compared to healthy controls did not differ in our studies ( Hapangama et al ., 2008 ; Hapangama et al ., 2009 ) while others have reported longer telomeres in PBMCs from women with endometriosis ( Dracxler et al ., 2014 ). The reason for this observed difference could be attributed to the influence of different demographic features known to affect PMBC TL such as age, BMI and ethnicity.…”
Section: The Endometriummentioning
confidence: 92%
“…Consistent with the potential role of TP53 in fibrogenesis in endometriosis, endometriotic cells are reported to have longer telomeres and higher telomerase expression. [111][112][113] In addition, miR-125b is found to be critical for FMT and fibrosis, and to promote fibroblast proliferation through suppression of TP53. 114 Remarkably, miR-125b upregulation has been reported in endometriosis.…”
Section: Tp53mentioning
confidence: 99%
“…Analysis of menstrual tissue samples from affected women showed that endometriosis patients have significantly more fragments of the basalis layer in the flow than healthy controls [70]. Cells from menstrual blood of patients also have longer than average telomeres, which is in agreement with an enhanced stem cell presence [71]. According to this model, long-lived stem cells from the basalis are disseminated and give rise to endometriotic lesions.…”
Section: Uterine Endometrial Stem Cellsmentioning
confidence: 61%